Determinant of Islamic Bank Stability and Risk-Taking Behavior in ASEAN - Riani, Ririn; Indra (SMART Insight, 2025)
This study examines the determinants of stability and risk-taking in ASEAN Islamic banks by focusing on both internal bank-specific factors and external conditions. Using a panel of 33 Islamic banks from five ASEAN countries over the period 2015–2022, this study employs a two-step system Generalized Method of Moments (GMM) estimator to address endogeneity and dynamic effects. Bank stability is measured using the Z-score, while risk-taking behavior is proxied by loan loss provisions. Internal factors include profitability, credit risk, efficiency, capitalization, liquidity, and bank size, while external factors comprise market concentration and macroeconomic indicators. The empirical results reveal three key findings. First, bank stability is primarily driven by bank-specific characteristics, with credit risk, efficiency, capitalization, bank size, and market concentration exerting significant effects, while macroeconomic variables remain insignificant. Second, risk-taking behavior exhibits strong persistence and is significantly influenced by both internal factors and macroeconomic conditions, particularly economic growth and inflation. Third, higher market concentration is associated with lower bank stability and greater risk-taking, supporting the competition–fragility hypothesis in the context of ASEAN Islamic banking. These findings provide important policy implications for regulators, Islamic banks, and deposit insurance authorities in the ASEAN region, emphasizing the need for strengthened microprudential supervision, risk-based regulatory frameworks, and enhanced internal governance to ensure sustainable financial stability within dual banking systems.